8-Oxo-7, 8-dihydro-2'-deoxyguanosine, reactive oxygen species and ambulatory blood pressure in African and Caucasian men: The SABPA study. (November 2014) - Mels, C. M.C.; Schutte, A. E.; Schutte, R.; Pretorius, P. J.; Smith, W.; Huisman, H. W.; van der Westhuizen, F. H.; Fourie, C. M. T.; van Rooyen, J. M.; Kruger, R.; Louw, R.; Malan, N. T.; et al.
Abstract Various studies indicate a relationship between increased oxidative stress and hypertension, resulting in increased DNA damage and consequent excretion of 8-oxo-7, 8-dihydro-2'-deoxyguanosine (8-oxodG). The aim of this study was to compare urinary 8-oxodG levels in African and Caucasian men and to investigate the association between ambulatory blood pressure (BP) and pulse pressure (PP) with 8-oxodG in these groups. We included 98 African and 92 Caucasian men in the study and determined their ambulatory BP and PP. Biochemical analyses included, urinary 8-oxodG, reactive oxygen species (ROS) (measured as serum peroxides), ferric reducing antioxidant power (FRAP), total glutathione (GSH), glutathione peroxidase (GPx) and glutathione reductase (GR) activity. The African men had significantly higher systolic (SBP) and diastolic blood pressure (DBP) (both p < 0.001). Assessment of the oxidative stress markers indicated significantly lower 8-oxodG levels (p < 0.001) in the African group. The African men also had significantly higher ROS (p = 0.002) with concomitant lower FRAP (p < 0.001), while their GSH levels (p = 0.013) and GR activity (p < 0.001) were significantly higher. Single and partial regression analyses indicated a negative association between urinary 8-oxodG levels with SBP, DBP and PP only in African men. These associations were confirmed in multiple regression analyses (SBP: R2 = 0.41; β = −0.25; p = 0.002, DBP: R2 = 0.30; β = −0.21; p = 0.022, PP: R2 = 0.30; β = −0.19; p = 0.03). Our results revealed significantly lower urinary 8-oxodG in African men, accompanied by a negative association with BP and PP. We propose that this may indicate a dose-response relationship in which increased oxidative stress may play a central role in the up-regulation of antioxidant defence and DNA repair mechanisms.